Kaj pomeni misliti? - Klun, Branko (Bogoslovni vestnik, 2024)
The title question recalls Heidegger's lectures of the same name and uses his existential-phenomenological method to problematise the dominant interpretation of thinking as mental processes performed by the human mind. The creators of artificial intelligence have set the goal that artificial intelligence should be able to mimic human thinking and, as a result, be able to carry out activities that can be called intelligent. But the attempt to reduce human thinking to logical operations and 'calculative thinking' (Heidegger) overlooks its existential character. For thinking is not just an attribute of human beings, it is an essential way in which we exist (i.e. a mode of existing). Therefore, the phenomenon of thinking cannot be adequately described in a third-person perspective (of the empirical sciences) but requires a first-person (phenomenological) reflection. The article is also critical of attempts to use the phenomenological approach as a means of developing artificial intelligence (Heideggerian AI) and advocates an understanding of thinking that is integrated into the totality of human existence, enabling it to achieve its fullness and authenticity.
Keywords: Artificial Intelligence; authenticity; calculative thinking; Dreyfus, Hubert; eksistencialna analiza; existential analysis; Heidegger, Martin; mišljenje; pristnost; računajoče mišljenje; thinking; umetna inteligenca